Punching speed boosting special training model for competitive karate - Orlov, Yu. L.; Sanauov, J. A. (Theory and Practice of Physical Culture, 2020)
Competitive performance analysis for elite karate has showed that one of the key reasons for the competitive failures is the underdeveloped sensorimotor qualities that may overshadow even the best fighting tactics. Imperfect timing, faulty amplitude and low speed of the punches give ample opportunities for the opponents to respond by defenses and counterattacks. Competitive success in the modern karate heavily depends on the attack speeds, amplitudes, footwork and accuracy. The competitive performance analyses in the Kumite karate discipline found the losses being due mostly to the delayed responses, poor timing, imperfect amplitudes and low speeds of the attacks. These deficiencies may be corrected by a new punching speed boosting special training model. The study data and analyses demonstrated benefits of the model making a special emphasis on the sensorimotor action stimulation and control component to effectively shape up and excel the situation-specific individual punching style for a relatively short time as verified by the athletes` progress in the sensorimotor fitness and punching efficiency rating tests.